Synthesis, Crystal Structure and Fluorescence Spectrum of a Europium Compound [Eu(NO3)3(H2O)4]·(C10H9N2)2·(NO3)2 - Chen, Xiao-Ju; Hu, Wei-Ji; Qin, Yi; Zhao, Guo-Liang (Asian Journal of Chemistry, 2013)
A europium compound with the general molecular composition [Eu(NO3)3(H2O)4]·(C10H9N2)2·(NO3)2 was synthesized from 4,4'-bipyridyl and Eu(NO3)3·6H2O in ethanol and characterized by elemental analysis, molar conductance, IR, TG and X-ray crystallographically. The single-crystal X-ray diffraction studies demonstrated that compound is crystallize in triclinic system, space group Pi, with a = 0.8112(3) nm, b = 1.2797(3) nm, c = 1.5164(2) nm, a = 95.158º, b = 101.732º, g = 100.174º, V = 1.504(2) nm3, Z = 2, Mr = 848.46, F(000) = 848.0, Dc = 1.873 g cm-3, μ (M0Ka) = 1.056 mm-1. It turned out that three nitrate anions coordinate to Eu(III) as bidentate and four water molecules coordinate to Eu(III), forming a ten-coordination distorted dicapped square antiprism geometry. In addition, the luminescent property and fluorescence quenching interaction with EB-DNA have been studied. CCDC: 871243.